Local heat transfer coefficient for pool boiling of R-134a and R-123 on smooth and enhanced tubes - Gorgy, Evraam; Eckels, Steven J. (My University, 2012)
The current paper presents experimental investigation of nucleate pool boiling of R-134a and R-123 on enhanced and smooth tubes. The enhanced tubes used were TBIIHP and TBIILP for R-134a and R-123, respectively. Pool boiling data were taken for smooth and enhanced tubes in a single tube test section. Data were taken at a saturation temperature of 4.44 °C. Each test tube had an outside diameter of 19.05 mm and a length of 1 m. The test section was water heated with an insert in the water passage. The insert allowed measurement of local water temperatures down the length of the test tube. Utilizing this instrumentation, local heat transfer coefficients were determined at five locations along the test tube. The heat flux range was 4-135 kW/m² for the TBIIHP tube and 5-60 kW/m² for the TBIILP tube. The resulting heat transfer coefficient range was 6,270-23,268 W/m².°C and 6,748-23,338 W/m².°C for both tubes, respectively. For smooth tube testing, the heat flux ranges were 7.3-130.7 kW/m² and 7.5-60.7 kW/m² for R-134a and R-123, respectively; with resulting heat transfer coefficient ranges of 1,798.9-11,379 kW/m².°C and 535.4-3,181.8 kW/m².°C. The study provided one of the widest heat flux ranges ever examined for these types of tubes and showed significant structure to the pool boiling curve that had not been traditionally observed. Additionally, this paper presented an investigation of enhanced tubes pool boiling models.
Keywords: Boiling heat transfer; Refrigerants pool boiling; Flooded evaporators; Enhanced tubes; Local heat transfer coefficient; Enthalpy based heat transfer analysis